Analisis Buku Teks Bahasa Arab Madrasah Ibtidaiyah Kelas 6 Terbitan Kementerian Agama Tahun 2020 Perspektif KMA RI No. 347 Tahun 2022 - Salma Roidah; Jauharotun Nafisah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2024)
This article aims to analyze the 6th-grade Arabic student textbook of Madrasah Ibtidaiyah, published by the Ministry of Religious Affairs in 2020, based on the perspective of KMA RI No. 347 of 2022. The research method used is a qualitative method, specifically a literature study. Data collection is carried out using the simak-record technique, and the data analysis method used is content analysis, which is sourced from two types of data. The primary data comes from the 6th-grade Arabic student textbook published by the Ministry of Religious Affairs in 2020, while the secondary data consists of a collection of related articles. The study's results indicate that the 6th-grade Arabic student textbook published by the Ministry of Religious Affairs in 2020 closely aligns with the standards outlined in KMA No. 347 of 2022. This book presents the material's content in an engaging manner, and it includes appropriate test exercises for evaluation.